The feed balances sheet: a tool for planning the use of resources and enhancing resilience in tropical grazing livestock - Mottet, Anne; Assouma, Mohamed Habibou (Frontiers in Animal Science, 2024)
Similarly to other tropical, arid and semi-arid regions of the World, lLivestock production in the Sahel is based on extensive grazing in rangelands where managing herd mobility (transhumance and nomadism) is key to productivity and sustainability. However, in this region, government planning, impact assessments and climate change adaptation solutions face several methodological limitations and lack of data availability particularly about the feed and forage resources and how there are used by livestock. Existing feed balances at national or regional level in Sub-Saharan Africa are still largely perfectible. To address these limitations, FAO and CIRAD (French Agricultural Research Centre for International Development) have developed a tool called Feed Balance Sheet (FBS) adapted to the Sahelian livestock systems to help countries carry out improved feed balances. This new FBS tool provides the following improvements to existing feed balances in countries: (i) it considers the seasonality of feed availability and quality as well as the seasonality of animal requirements; (ii) it includes protein and energy in addition to dry matter; (iii) it takes into account a wide range of resources, including browsing of woody biomass. This article describes the methodological development and the assumptions underlying this tool, which has already been piloted in 6 countries in Western and Central Africa. It also presents the results from 2 countries (Mali and Chad) and draws conclusions on the tool's relevance and guidance for its application.It can be used to improve the resilience of pastoral communities in the Sahel and better plan responses to droughts and other types of crises. Its use requires dedicated training and partnerships between governments and science organizations for accessing the appropriate input data. Based on the tool's experience in six countries (including 2 for which results are presented in this paper), we have confirmed the key role that CIRAD, FAO and their partners must play during the first few years in coaching the different teams at the country level.